Foundational Holism, Substantive Theory of Truth, and A New Philosophy of Logic: Interview with Gila Sher BY Chen Bo. - Sher, Gila; Bo, Chen (Philosophical Forum, 2019)
An interview with the Gila Sher, professor at the Peking University in Beijing, China. Topics discussed include information on the philosophy of education and the educational ideologies; presents his views on Epistemic Friction: An Essay on Knowledge, Truth and Logic; and the information on the her essential contribution to epistemology, the theory of truth, and the philosophy of logic.